Analisis Kinerja Koperasi Unit Desa di Daerah Istimewa Yogyakarta - SIREGAR, Abi Pratiwa ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to (1) determine the financial performance of village unit cooperative/Koperasi Unit Desa (KUD) in Yogyakarta Special Region (2) determine the affecting factors of profit/selisih hasil usaha (SHU) (3) determine the institutional performance of village unit cooperative in Yogyakarta Special Region. The basic method used for this study is descriptive analysis. The data used are the primary and secondary data. Data primary obtained through the interview while data secondary obtained through KUDâs annual report from 2011 until 2012. Sampling method is purposive sampling, based on the highest profitâs value in each KUD in regency or city in Yogyakarta Special Region in 2012, any KUD in each regency or city taken 4 people respondents, 3 people of board organizer, and 1 inspector of each KUD. Methods of analysis used financial ratio analysis to determine financial performance of village unit cooperative in Yogyakarta Special Region, multiple regression analysis to determine the affecting factors of profit, and analysis efforts to determine the institutional performance of village unit cooperative in Yogyakarta Special Region. The result showed that financial performance of village unit cooperative in Yogyakarta Special Region still low. The significant factors for affecting profit are business volume, dummy USP, dummy RMU, dummy electricity